The Personality Traits and Interactive Behavior of Chinese Mitten Crab (Eriocheir sinensis) - Jianyang Sun; Dongxin Zhang; Yuhang Hong; Chengyi Weng; Yangyang Pang; Yongxu Cheng; Xiaozhen Yang (Fishes)
Agonistic behavior is a common behavior among agonistic Chinese mitten crabs (Eriocheir sinensis). Such behavior often leads to limb loss or physical impairment, and significantly affects the survival, growth, and quality of the crabs, and even the yield and economic value for E. sinensis. Agonistic behavior often occurs in agonistic crabs, which is closely related to personality traits and interactive behavior of animals. E. sinensis has personality traits such as boldness, aggression, and exploration as evidenced by the partition-crossing experiment, mirror experiment, and shelter experiment. Agonistic crabs were identified as individuals with boldness, high aggression, and high exploration. The interactive behavior spectrum of E. sinensis was first obtained, consisting of 15 behaviors. This spectrum described and summarized all interactive behaviors of E. sinensis during fights. The interactive behavior characteristics of agonistic crabs were identified as darting, intimidating, grabbing, pushing, stretching, and visitation. These results lay a theoretical basis for in-depth behavioral research on E. sinensis in the future. The technique of identifying agonistic crabs by personality traits and interactive behaviors not only allows for the elimination of agonistic crabs from the aquaculture process and the reduction in negative impacts caused by aggressive crabs, but also allows for the breeding of non-agonistic crabs and the further reduction in the economic losses caused by fighting behaviors.